Soropositividade feminina e atendimento oferecido: articulando sentidos - Santos, Lívia Andrade (2009)
This study aimed to understand the process of constructing meanings on female seropositivity and the care offered to these women through interpretative repertoires. We interviewed 14 professionals of different specialties that comprise a health team in a city within the Triângulo Mineiro. Discourse analysis as proposed by social constructionism was used. A full transcription of interviews and careful reading of the material, which allowed the pointing out of the repertoires were performed. During analysis, it was observed that the meanings of the seropositive women significantly influenced the descriptions of care offered, and so recognizing a conjunction of meanings. Therefore, a division of repertoire analysis was performed in two moments: (1) in which they talk about women bearing the disease, infection and their experience with the disease and (2) in which they talk about the service. We observed how the professionals in their daily actions described, discussed and constructed meanings on seropositive women and their care from theoretical concepts disseminated by epidemiology. These repertoires were named as: (1) Two women, victims and guilty, (2) Irresponsible women, (3) Women who have difficulty in negotiating condoms and (4) Women who live in a vulnerable context. We can say that when these professionals talk about female seropositivity, the discourse of epidemiology goes beyond the issues of prevention, to the experience of the disease and the care offered. Each discourse retaken to talk about female seropositivity promoted different assistance strategies for these women. At the same time, we perceived that this practice does not track the movement of the epidemiology and discursive discussions in general health. There is difficulty in recognizing the situation of vulnerability of these women, from the use of other discourses in which the broad concept of "risk" is involved. The use of this concept promotes the omission of the participation of men when speaking of female seropositivity and the care that is offered. When the vulnerability context is recognized, the discourse of professionals does not include the service and health policies that guide these women. Furthermore, we recognize that this is a practice still marked by the biomedical model and professional expertise. It was possible to reflect on how the concepts of epidemiology are embedded and appropriated by health professionals specialized in HIV/AIDS and their implications for health care assistance.